New Firm Formation and Industry Growth : Does Having a Market- or Bank-Based System Matter? - Beck, Thorsten (World Bank, Washington, DC, 2014)
The authors find no evidence for the superiority of either market-based or bank-based financial systems for industries dependent on external financing. But they find overwhelming evidence that industries heavily dependent on external finance grow faster in economies with higher levels of financial development, and with better legal protection for outside investors - including strong creditor and shareholder rights and strong contract enforcement mechanisms. Financial development also stimulates the establishment of new firms, which is consistent with the Schumpeterian view of creative destruction. Financial development matters. That the financial system is bank-based on market-based offers little additional information.